GAGASAN PENGATURAN LARANGAN PENJUALAN ROKOK ELEKTRIK/VAPE BAGI ANAK DI BAWAH UMUR 18 TAHUN DIKATKAN DENGAN UNDANG-UNDANG NOMOR 17 TAHUN 2023 TENTANG KESEHATAN - Hutabarat, Memory Jesaya; Junaidi, Junaidi; Akmal, Zainul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Indonesia is the third largest cigarette consumer in the world. As time goesby, technology continues to develop, not all cigarette products today only usetobacco as raw materials. Nowadays, many consumers are switching fromconventional cigarettes to electronic cigarettes. Electronic cigarettes, which are aninnovation from conventional cigarettes to electronic cigarettes which consist oftwo elements, namely a suction device and liquid (refill). E-cigarettes areconsidered safer than regular cigarettes. It turns out that the risk of inhaling e-cigarettes is not much different from regular cigarettes. The journal published byCirculation stated that high amounts of nanoparticles were found in e-cigarettevapor inhalers. In the absence of warning labels, danger labels and standardizationof e-cigarettes sold by business actors, the rights of e-cigarette buyers/users asconsumers have been violated, such as the right to security and safety in consuminggoods and/or services and the right to information provided. correct, clear andhonest regarding the condition of the goods.This research is a normative legalresearch.This research method uses a type of normative legal research using legalsynchronization analysis, using primary legal materials such as Law Number 17 of2023, Government Regulation Number 109 of 2012 concerning Handling ofMaterials Containing Addictive Substances in the Form of Tobacco Products forHealth, and legal materials other. This research also uses qualitative data analysisand produces descriptive data.There are conclusions obtained, namely: First, the regulations regardingelectronic cigarettes in Indonesia, both in terms of sales and use, do not yet haveclear regulations. The connotation of cigarettes referred to in Indonesian laws andregulations is defined as conventional cigarettes. The only regulation on electroniccigarettes in Indonesia is regulated only through the Regulation of the Minister ofTrade of the Republic of Indonesia Number 86 of 2017 concerning Provisions forthe Import of Electric Cigarettes. There are no specific regulations regarding theprohibition on the use of e-cigarettes, which clearly also pose dangers, especiallyto people's health rights which are protected by the constitution. Second, a ban onthe sale of cigarettes is an inevitability that must be implemented.Keywords: E-Cigarette – Health – Legal Ideas.